THE HUMAN BEHAVIOR IN SAMKHYA’S TEACHING: ETHICS PERSPECTIVE - Arniati, Ida Ayu Komang (International Conference on Cultural Studies, 2018)
Samkhya is the oldest school that trying to harmonize the Vedic philosophy scriptures through the rational mind. Samkhya explains the cosmic evolutionary process of the universe. The term Samkhya comes from a word which means the amount of numbers to calculate the cosmic evolutionary principles in a rational way. Samkhya teaches dualism knowledge that makes possible the distinction between soul and body (spirit-objects) or Purusa and Prakerti consisting of 25 categories. Purusa and Prakerti are composed of tri-use ethics of sattwa, rajas, and tamas. These three gunas are in equilibrium (samyavastha). Prakerti requires the presence of Purusha to be known and appreciated, and Purusha requires the assistance of prakerti to distinguish itself from prakerti to obtain deliverance (kaivalyartham).